2017
DOI: 10.1519/jsc.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Assessing Muscle Power During the Standing Cable Wood Chop Exercise

Abstract: Zemková, E, Cepková, A, Uvaček, M, and Šooš, L. A novel method for assessing muscle power during the standing cable wood chop exercise. J Strength Cond Res 31(8): 2246-2254, 2017-The study estimates the repeatability and sensitivity of a novel method for assessing (a) the maximal power during the standing cable wood chop exercise with different weights and (b) the endurance of the core muscles. A group of 23 fit men performed (a) maximal effort single repetitions of the standing cable wood chop exercise with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Previous studies have not identified significant differences in peak torque in strength testing, or in total work in the rotational endurance testing between the dominant and non-dominant side in healthy golfers, control group and golfers with low back pain [19]. Likewise, there were no significant differences in the mean power produced during the standing cable wood chop exercise on the left and the right side with all weights used in a group of fit healthy men [39]. Taking these findings into account, we assumed no side-to-side differences in trunk rotational velocity in healthy, fit able-bodied athletes, but the question remained regarding such differences in para table tennis players.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have not identified significant differences in peak torque in strength testing, or in total work in the rotational endurance testing between the dominant and non-dominant side in healthy golfers, control group and golfers with low back pain [19]. Likewise, there were no significant differences in the mean power produced during the standing cable wood chop exercise on the left and the right side with all weights used in a group of fit healthy men [39]. Taking these findings into account, we assumed no side-to-side differences in trunk rotational velocity in healthy, fit able-bodied athletes, but the question remained regarding such differences in para table tennis players.…”
Section: Discussionmentioning
confidence: 81%
“…Likewise, there were no significant differences in mean power produced during the standing cable wood chop exercise on the left and the right side with all weights used in a group of fit healthy men (Zemková et al, 2016). Therefore, we assumed no side-to-side differences in power outputs in participants of the present study and used average values of better trial on each side for data analysis.…”
Section: Discussionmentioning
confidence: 97%
“…The test adapted from the wood chop exercise provides conditions similar to those imposed in many sports involving trunk rotation in standing position (baseball, golf, karate, etc.). Recent study showed that evaluation of maximal muscle power and trunk rotational endurance during the standing cable wood chop exercise on a weight stack machine is both a reliable method and sensitive to differences among physically active individuals (Zemková, Cepková, Uvaček, & Šooš, 2016). Specifically, mean rotational power is reliable (ICC values above 0.90 at all weights tested) and sensitive parameter able to discriminate within-group differences.…”
Section: Introductionmentioning
confidence: 99%
“…Seven exercises, two static ('Bird dog', 28 43-45 'Wall squat' 46 47 ) and five dynamic ('Flexion/extension control quadruped', 48 'Half circle in side lying', 38 'Sitting side flexion (mermaid)', 49 'Upper back rotation with lunges' 50 and 'Standing wood chop/chop and lift' [50][51][52][53] ) were identified as specific for promoting motor control and maintaining spinal integrity during skilled movement (see table 2). A notable gap was exercises specific to segmental stabilisation.…”
Section: Motor Control Exercisesmentioning
confidence: 99%
“…Segmental movement control exercises included 'Flexion/extension control quadruped', 48 'Half circle in side lying', 38 'Sitting side flexion (mermaid)' 49 with each aiming to improve dynamic control of thoracic spine movement around all three motion planes. Whole body coordination exercises included 'Upper back rotation with lunges' 50 and 'Standing wood chop/chop and lift' [50][51][52][53] to improve dynamic control of thoracic spine movements in conjunction with movements of other parts of the kinetic chain. As with mobility, performance of many of the included exercises is dependent on the integrity and functional musculoskeletal capacity of other regions, for example, 'Standing wood chop/chop and lift'.…”
Section: Motor Control Exercisesmentioning
confidence: 99%